2020
DOI: 10.1080/09540105.2020.1724895
|View full text |Cite
|
Sign up to set email alerts
|

Broad-specific monoclonal antibody based IACs purification coupled UPLC-MS/MS method for T-2 and HT-2 toxin determination in maize and cherry samples

Abstract: In this work, broad-specific monoclonal antibody based immunoaffinity columns (IACs) coupled to ultra-high performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) for purification and determination of T-2 and HT-2 toxin in maize and cherry samples. Based on broad-specific anti-T-2 monoclonal antibody, the prepared IACs could be used for both T-2 and HT-2 purification with cross reactivity values at 100% for T-2 and 108% for HT-2. Column capacity was 3.14 μg mL −1 gel for T-2 toxin, and 3.20 μg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…For in-house fabricated IACs, antibodies coupled to solid supports have been packed in empty SPE columns. Com-monly, monoclonal antibodies against aflatoxins, DON, OTA, ZEN, T-2, and sterigmatocystin (STER) were used [71][72][73]. Contrary to widely commercialized IACs, AACs have been mainly prepared in laboratories to analyze aflatoxins and OTA [74,75].…”
Section: Home-made Cartridgesmentioning
confidence: 99%
“…For in-house fabricated IACs, antibodies coupled to solid supports have been packed in empty SPE columns. Com-monly, monoclonal antibodies against aflatoxins, DON, OTA, ZEN, T-2, and sterigmatocystin (STER) were used [71][72][73]. Contrary to widely commercialized IACs, AACs have been mainly prepared in laboratories to analyze aflatoxins and OTA [74,75].…”
Section: Home-made Cartridgesmentioning
confidence: 99%
“…To immobilize Abs on a solid sorbent, the most common approach is with regard to their covalent bonding, which is often achieved by coupling an accessible amino group of the Abs with a support that contains reactive groups such as epoxy [ 93 ] or aldehyde [ 97 ] or groups that can be activated using glutardialdehyde [ 71 , 100 , 101 ], carbonyldiimidazole, cyanogen bromide (CNBr) or N-hydrosuccinimide (NHS). Some activated supports are commercially available such as NHS- [ 70 ] or CNBr- [ 69 , 76 , 84 , 85 , 86 , 87 , 88 , 91 , 94 , 95 , 96 , 103 , 112 ] activated Sepharose or glutardialdehyde activated silica [ 74 , 77 , 82 ]. Non-covalent binding can also be used to couple Abs to the sorbent.…”
Section: Immunoaffinity Sorbentsmentioning
confidence: 99%
“…Reported or calculated dilution factor values are mainly between 2 and 10. It is worthwhile noticing that a residual amount of solvent in the extract can sometimes be necessary to ensure the complete solubilization of the toxins [ 74 , 77 , 84 , 85 , 86 , 94 , 95 , 96 ]. Moreover, some authors suggested to optimize the extraction conditions of the toxins from the sample not only regarding the final extraction recovery of the toxins but also by studying the effect of the nature of the extraction solvent on the final selectivity measured by the removal of the interfering peak in the final chromatogram.…”
Section: Immunoaffinity Sorbentsmentioning
confidence: 99%
See 2 more Smart Citations